Adaptor protein controlled oligomerization activates the AAA+ protein ClpC - Kirstein, Janine (2006)
The AAA+ protein ClpC is not only involved in the removal of misfolded and aggregated proteins but also controls, through regulated proteolysis, key steps of several developmental processes in the Gram-positive bacterium Bacillus subtilis. In contrast to other AAA+ proteins, ClpC is unable to mediate these processes without an adaptor protein like MecA. Here, we demonstrate that the general activation of ClpC is based upon the ability of MecA to participate in the assembly of an active and substrate-recognizing higher oligomer consisting of ClpC and the adaptor protein, which is a prerequisite for all activities of this AAA+ protein. Using hybrid proteins of ClpA and ClpC, we identified the N-terminal and the Linker domain of the first AAA+ domain of ClpC as the essential MecA interaction sites. This new adaptor-mediated mechanism adds another layer of control to the regulation of the biological activity of AAA+ proteins.